2019
DOI: 10.3746/pnf.2019.24.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic BSH Activity and Anti-Obesity Potential of Lactobacillus plantarum Strain TCI378 Isolated from Korean Kimchi

Abstract: Lactobacillus (Lab.) is a human probiotic beneficial for the prevention and improvement of disease, yet properties of different Lab. strains are diverse. To obtain a Lab. strain that possesses greater potential against gastrointestinal dysfunction, we isolated Lactobacillus plantarum TCI378 (TCI378) from naturally fermented Korean kimchi. TCI378 has shown potential as probiotic since it can survive at pH 3.0 and in the presence of 0.3% bile acid. The bile salt hydrolase activity of TCI378 was shown by formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…International studies shown that Lactobacillus plantarum had a quite substantial BSH-activity (Huang et al, 2019;Kumar, Grover & Batish, 2012;Ren, Sun, Wu, Yao & Guo, 2011;Tsai et al, 2014). In our present trial we also revealed, using quantitively assessment method (Huijghebaert & Hofmann, 1986;Joyce et al, 2014), a quite high BSH activity of investigational capsules containing 2*109 CFU in one capsule, that confirm and expand the literature data (Huang et al, 2019;Kumar et al, 2012;Ren et al, 2011;Tsai et al, 2014).…”
Section: A B Csupporting
confidence: 91%
See 2 more Smart Citations
“…International studies shown that Lactobacillus plantarum had a quite substantial BSH-activity (Huang et al, 2019;Kumar, Grover & Batish, 2012;Ren, Sun, Wu, Yao & Guo, 2011;Tsai et al, 2014). In our present trial we also revealed, using quantitively assessment method (Huijghebaert & Hofmann, 1986;Joyce et al, 2014), a quite high BSH activity of investigational capsules containing 2*109 CFU in one capsule, that confirm and expand the literature data (Huang et al, 2019;Kumar et al, 2012;Ren et al, 2011;Tsai et al, 2014).…”
Section: A B Csupporting
confidence: 91%
“…International studies shown that Lactobacillus plantarum had a quite substantial BSH-activity (Huang et al, 2019;Kumar, Grover & Batish, 2012;Ren, Sun, Wu, Yao & Guo, 2011;Tsai et al, 2014). In our present trial we also revealed, using quantitively assessment method (Huijghebaert & Hofmann, 1986;Joyce et al, 2014), a quite high BSH activity of investigational capsules containing 2*109 CFU in one capsule, that confirm and expand the literature data (Huang et al, 2019;Kumar et al, 2012;Ren et al, 2011;Tsai et al, 2014). After 12 weeks of our investigation it was shown that additional supplementation with probiotic L. plantarum led to statistically significant increasing of RA of gut bacterial BSH in patients with dyslipidemia that was similar to healthy adults without dyslipidemia.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a probiotic mixture containing B. animalis VLK and VKB and L. casei IMV B-7280 increased the levels of IL-4, IL-10 and TGF-β in rats with monosodium glutamate-induced obesity (Falalyeyeva et al, 2017). In this vein, L. plantarum was shown as a promising strain for the reduction of hypercholesterolemia and adipogenesis in vitro experiments (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Some of the reported beneficial effects of probiotics in human health include anticancer [99][100][101][102][103][104][105][106][107][108][109][110][111], anti-allergic [112,113], anti-diabetic [114][115][116], anti-obesity [117][118][119][120], anti-pathogenic [121,122], immunomodulatory [123], and anti-inflammatory [124][125][126][127] activities [128], as reported in Table 1.…”
Section: Health Promoting Effect Of Prebiotics Probiotics and Synbimentioning
confidence: 99%